"All unfortunate young women are lyrical poets" (Romanian women voices from abroad) (Philologia, 2021)
The paper focuses historically on the contributions of women in exile to both Romanian literature and Romanian politics throughout more than a century, beginning with the second half of the 19th century and going on throughout the 20th. The main writers mentioned in the articles are Elena Vacarescu, Anne de Noailles, Marthe Bibesco and Monica Lovinescu.
Keywords: literature; culture; gender studies; women's writings; multiculturalism